Penggunaan Media Flash Card dalam Meningkatkan Kemampuan Literasi Membaca Siswa pada Materi Aku Berperilaku Pancasila di Kelas II SDN 03 Mojo - Fatkhi Fiddin, Abdullah; Purbasari, Imaniar; Rondli, Wawan Shokib (Mataram University, 2025)
This study aims to determine the effectiveness of using flash card media on the reading literacy skills of second-grade students at SDN 03 Mojo in the topic